Urgensi Sejarah al-Qur’an dalam Pendidikan Islam - Erwin Padli (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2020)
This research is a literature review related to the history of the Qur'an, from history to history and bookkeeping. This study aims to examine the importance of the history of the Qur'an in Islamic education. Apart from being the main source of Muslim diversity, the Qur'an also contains education. In reality, it is not only the contents of the Qur'an that contain education but from the history of decline to the bookkeeping, there are educational values ??that can be learned and can be applied. For example, the history of the Golden Islamic civilization is not from the Qur'an. The advances that have occurred are supported by a high understanding of the Qur'an. To produce civilization or thoughts that are directed to the benefit of humans. With the Koran breathing, the development of education and even Islamic civilization can reach its peak.